Demographic Analysis on Self-Regulation among Malaysian University Students during the Covid-19 Pandemic - Norsimah Dasan; Norkiah Arsat; Mohd Mahadzir Rahimi Mohamed Nawi (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2022)
The Covid-19 pandemic has had a major impact on the lives of the entire population of the world. The effect is also experienced by university students who must be independent in learning. Therefore, self-regulation is needed in the management of their life at the university. The concept of self-regulation is an individual's belief about his ability to plan and control behavior. Students at university need these factors to ensure that the patterns of thinking and feeling produced are in line with their actions of completing tasks and at the same time control their behavior from harmful social and environmental effects. Demographic factors such as gender, ethnicity, place of residence of students, field of study and duration of study are focused as variables that are assumed to influence differences in student self-regulation. This study was conducted using a quantitative method involving 590 students of Universiti Malaysia Sabah who were selected through random sampling. The Adolescent Self-Regulation Inventory instrument was used to obtain feedback from the sample. Data were analyzed using IBM SPSS 26.0 software. The results of the study found that selfregulation does not differ significantly based on gender, ethnicity, student's place of residence, field and period of study. This study contributes to the addition of psychological knowledge related to student self-regulation during the Covid-19 pandemic